Prevalence of Vitamin D Deficiency in Children with Fractures: Before and during the COVID-19 Outbreak. (22nd June 2022) - Lee, Yong-Suk; Lee, Sang-Uk; Hong, Tae Min; Joo, Sun Young
Abstract : Background . Although it is generally agreed that vitamin D is important for bone health, the role of vitamin D in preventing fractures in children and adolescents remains unclear. Therefore, this study aimed to investigate the prevalence of vitamin D deficiency and insufficiency in healthy Korean children with fractures. Our secondary aim was to compare serum vitamin D levels before and during the coronavirus disease 2019 (COVID-19) outbreak. Methods . We evaluated 334 patients with fractures who were surgically treated at our institution between 2018 and 2019 before the onset of COVID-19 (group I). In addition, we collected data on the serum 25(OH)D levels of 210 patients who visited our pediatric department for evaluation of short stature (group II) and the serum 25(OH)D levels of the patients with fractures during the COVID-19 pandemic period (group III). A serum 25(OH)D level of <20 ng/mL was considered deficient, between 20 and 32 ng/mL was insufficient, and ≥32 ng/mL was considered sufficient. Results . The mean age was 8.1 ± 3.5 years in group I, 8.2 ± 3.7 years in group II, and 8.6 ± 3.5 years in group III. The prevalence of vitamin D deficiency was 53.0% in group I and 32.9% in group II. The mean serum 25(OH)D level was lower in group I than in group II (20.0 ± 7.3 ng/ml vs. 23.2 ± 6.9 ng/ml, p < 0.001 ). The mean serum 25(OH)D level of younger patients (<10 years) in group III was lower than that of the younger patients in the prepandemic period (21.4 ± 7.2 ng/mL vs. 19.2 ± 6.8 ng/mL, p = 0.037 ). Conclusions . We observed a high prevalence of vitamin D deficiency/insufficiency in children with fractures who required surgical treatment. During the COVID-19 pandemic, the serum vitamin D levels became even lower, especially in younger children.